ANALISIS USAHA PENGOLAHAN TRADISIONAL IKAN KERING DI DESA JANGKAR KABUPATEN SITUBONDO - Ika Junianingsih (Faculty of Science and Technology University Ibrahimy, 2014)
The purpose of this study was to determine and analyze the value of dry fish processing business profitability. Profitability analysis effort is made to measure how effective / efficient an attempt to make a profit by using resources (resources) that exist. The research was conducted from October to December 2013 in the Village Anchor, Situbondo. Stages of research conducted through direct interviews (depth interview) to key persons (processors), using a semi-structured questionnaire, followed by drying business financial feasibility studies. Test methods for the analysis of business profitability dried fish is done by calculating the value of profits, the ratio of R / C, and the ROI. The results showed that the capital used by dry fish processing business is for Rp.132.600.000, - / year with receipts of Rp.144.000.000, - / year and the benefits of Rp.11.400.000, - / year , The result of the calculation of the ratio of R / C at 1:08 indicate that dry fish processing business is profitable to develop. As for the value ROI of 8:59% / year showed that dry fish processing business is less efficient in the recovery of capital investment. The condition is caused profits decreased due to the growing production costs while sales prices are relatively fixed.